Acute Large Bowel Obstruction Following Late Sequelae of Traumatic Diaphragmatic Hernia - Hasan, Md Mahboob; Baqui, MA; Rahman, Farzana; Hasan, Merajul (Journal of Armed Forces Medical College, Bangladesh, 2020)
A 33 years old patient was admitted in a Military Hospital with the features of acute large gut obstruction. Exploratory laparotomy was done and peroperatively the obstruction was seen in the transverse colon and obstruction seemed to be carcinoma of transverse colon with involvement of left hemidiaphragm which was not negotiable. Transverse loop colostomy with decompression of bowel was done. Subsequently the patient was transferred to tertiary level hospital in Dhaka. In the tertiary hospital, the patient developed left sided massive pleural effusion. With relevant investigation the condition was diagnosed as left sided diaphragmatic hernia. Thoracotomy was done and herniorrhophy was performed after reduction of the content. Post-operative management was stormy and eventful but the condition improved gradually and the patient was discharged in proper time. The patient had history of chest trauma due to RTA he met 4 years back and he received hospital indoor management for 3½ months. The patient was asymptomatic and leading normal active military life before 2nd time admission for acute intestinal obstruction. The patient had past history of trauma to left chest wall 4 years back, presented with acute large gut obstruction and there was diagnostic dilemma. There were management difficulties and post operative events were stormy. The aim of this reporting is to highlight all of these. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 119-120